A Golgi and tonoplast localized S‐acyl transferase is involved in cell expansion, cell division, vascular patterning and fertility in Arabidopsis. Issue 2 (25th June 2013) - Qi, Baoxiu; Doughty, James; Hooley, Richard
Summary: S ‐acylation of eukaryotic proteins is the reversible attachment of palmitic or stearic acid to cysteine residues, catalysed by protein S ‐acyl transferases that share an Asp‐His‐His‐Cys (DHHC) motif. Previous evidence suggests that in Arabidopsis S ‐acylation is involved in the control of cell size, polarity and the growth of pollen tubes and root hairs. Using a combination of yeast genetics, biochemistry, cell biology and loss of function genetics the roles of a member of the protein S ‐acyl transferase PAT family, AtPAT10 (At3g51390), have been explored. In keeping with its role as a PAT, AtPAT10 auto‐ S‐ acylates, and partially complements the yeast akr1 PAT mutant, and this requires Cys 192 of the DHHC motif. In Arabidopsis AtPAT10 is localized in the Golgi stack, trans‐Golgi network/early endosome and tonoplast. Loss‐of‐function mutants have a pleiotropic phenotype involving cell expansion and division, vascular patterning, and fertility that is rescued by wild‐type AtPAT10 but not by catalytically inactive AtPAT10C 192 A. This supports the hypothesis that AtPAT10 is functionally independent of the other Arabidopsis PATs. Our findings demonstrate a growing importance of protein S ‐acylation in plants, and reveal a Golgi and tonoplast located S ‐acylation mechanism that affects a range of events during growth and development in Arabidopsis.